1982
DOI: 10.1111/j.1744-7348.1982.tb01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to metalaxyl of Phytophthora infestans populations in potato crops in south‐west England in 1980 and 1981

Abstract: S U M M A R YA laboratory test was developed to assess the sensitivity of field populations of Phytophthora infestans to metalaxyl. Discs of potato leaf tissue were floated upon solutions of the fungicide at different concentrations and inoculated with spores. The extent of symptom development was noted after incubation under standard conditions for 5-6 days. In preliminary experiments growth of isolates of P. infestans obtained from culture collections was severely inhibited in discs treated at 2 pglml. By co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Each sample was collected from an individual field or potato storage facility. 4 Number of isolates of P. infestans obtained from individual late blight lesions found on samples in that province.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sample was collected from an individual field or potato storage facility. 4 Number of isolates of P. infestans obtained from individual late blight lesions found on samples in that province.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to metalaxyl in Europe developed soon after the chemical was introduced in the early 1980s (4,8,10,16). Metalaxyl resistance also occurs in isolates from the Middle East (7), Asia (36,51), Mexico (37), South America (20), and the United States (12,38).…”
mentioning
confidence: 98%
“…However, no resistant isolates were found in 1981 crops in south-west Scotland grown from Irish seed. Carter et al (1982) also could not account for resistant/", infestans in crops in south-west England in terms either of wind-borne sporangia or infected seed. The third, and most hkely possibility on the evidence available, is that resistant strains were present in the endemic population of P-infestans.…”
Section: Discussionmentioning
confidence: 95%
“…In Northern Ireland, where no problems were reported on the foliage, Cooke (1981) obtained resistant isolates from tubers from six of nine crops sprayed with metalaxyl + mancozeb, and from two which were sprayed with metalaxyl on its own. In England and Wales, limited monitoring of crops, mainly in south-west England (Carter et al, 1982), detected no resistance. No monitoring was done in Scotland in 1980.…”
Section: Introductionmentioning
confidence: 99%
“…Experience with potato blight, caused by Phytophthora infestans (Mont.) de Bary, has also shown that resistant isolates which occur naturally are just as fit to survive in the absence of metalaxyl as sensitive isolates (Cooke, 1981;Carter et al, 1982). These findings emphasize the importance of avoiding resistance.…”
Section: Introductionmentioning
confidence: 98%